High-rate capability of spinel LiNi0.05Mn1.95O4 cathode for Li-ion batteries prepared via coprecipitated precursor - 孙斌 申国培 胡燕龙 (Transactions of Nonferrous Metals Society of China, 2007)
Spinel LiNi0.05Mn1.95O4 cathode material for lithium ion batteries was synthesized by solid-state reaction from coprecipitated Ni-Mn hydroxide precursors and characterized by X-ray diffraction（XRD）, scanning electron microscopy（SEM） and galvanostatic charge-discharge tests. It is found that LiNi0.05Mn1.95O4 powder has an ordered cubic spinel phase （space group Fd3m） and exhibits superior rate capability. After 450 cycles, the LiNi0.05Mn1.95O4/carbonaceous mesophase spheres（CMS） Li-ion batteries can retain 96.0% and 93.3% capacity at 5C and 10C charge/discharge rate, respectively, compared with 85.3% （5C） and 80.5% （10C） retention for LiMn204 batteries. However, the initial discharge capacity of LiNi0.05Mn1.95O4/CMS batteries at 1C charge/discharge rate （96.20 mA.h/g） is slightly lower than that of the LiMn2O4 batteries （100.98 mA.h/g） due to the increased average oxidation state of Mn inLiNi0.05Mn1.95O4.